An investigation of fretting behavior of thermoplastic polyurethane for mechanical seal application. (December 2018) - Wang, C.; Hausberger, A.; Berer, M.; Pinter, G.; Grün, F.; Schwarz, T.
Abstract: For seals in dynamic applications, fretting is one of the most common types of failure. In this study, the fretting behavior of thermoplastic polyurethane (TPU) was investigated. The hysteresis behavior, wear scar and coefficient of friction were analyzed in detail. Various wear mechanisms and their influences on the fretting behavior were examined. A new method was introduced to calculate the coefficient of friction for late cycles in gross slip regime. It takes the surface damage and the dynamic influence of the test system into consideration. Besides, the dependency of fretting behavior on displacement amplitudes, normal loads were investigated. Highlights: Investigation of fretting behavior of thermoplastic polyurethane (TPU). Introduction of a new method to calculate the coefficient of friction for late cycles in gross slip regime. It takes the surface damage and the dynamic influence of the test system into consideration. Analysis the fretting behavior with hysteresis behavior, wear scar and coefficient of friction.